Viral 2A-peptides mediate continuous transcription and self-cleavage of multiple heterologous genes in fowlpox virus vector - RAJASEKARAN, RANJANI; KIRUBAHARAN, J JOHN; SHILPA, P; VIDHYA, M; RAJALAKSHMI, S (The Indian Journal of Animal Sciences, 2021)
Applicability of viral 2A-peptides in generation of multi-cistronic transcripts to deliver separate self-cleaved proteins is well established. However, the use of viral 2A-peptides in fowlpox virus vector construction to co-express multiple heterologous genes has not been explored. To evaluate the same, a recombinant transfer plasmid pJFWPVt was constructed through two intermediate plasmid constructs, pJF7F9 and pJFHNGFP. The construction of pJF7F9 involved cloning of F7 and F9 genes of FWPV into pCI-neo with modifications in the F7-F9 intergenic region. For the construction of pJFHNGFP, a synthetic DNA adapter consisting of one synthetic early late promoter (PE/L), two viral 2A-peptides (P2A and T2A) and three multiple cloning sites (MCS1, MCS2 and MCS3) was synthesized chemically and was cloned into pUC19 to obtain pJFHNGFPi. Heterologous genes fusion (F) and haemagglutininneuraminidase (HN) of Avian Avulavirus-1 (AAv1) and marker gene AcGFP were cloned sequentially into MCS1, MCS2 and MCS3 of pJFHNGFPi to obtain pJFHNGFP. The insert (PE/L-F-P2A-HN-T2A-AcGFP) in pJFHNGFP was cloned into pJF7F9 to obtain pJFWPVt, which upon transfection in FWPV infected chicken embryo fibroblast (CEF) cells resulted in fluorescence. This confirmed the expression of AcGFP and the continuous transcription ability of viral 2A-peptides. Further, western blotting of CEF pellet showed separate protein bands of F and HN protein at 66 kDa and 74 kDa respectively, which confirmed the self-cleaving ability of viral 2A-peptides. Herein, in FWPV vector construction, continuous transcription and self-cleaving ability of viral 2A-peptides in FWPV vector construction was confirmed. This warrants scope for future viral 2A-peptide based FWPV vector construction.